Mesenchymal stromal cell implantation for stimulation of long bone healing aggravates Staphylococcus aureus induced osteomyelitis - Seebach, Elisabeth; Holschbach, Jeannine; Bitsch, Rudi G.; Kleinschmidt, Kerstin; Richter, Wiltrud (Acta biomaterialia, 2015)
Large bone defects requiring long-term osteosynthetic stabilization or repeated surgeries show a considerable rate of infection. Mesenchymal stromal cells (MSCs) have been successfully used to enhance bone regeneration, but their powerful immunomodulatory effects may impose an enhanced risk for osteomyelitis development. In order to unravel whether implantation of MSCs aggravates a simultaneous bone infection, a hydrogel-supported osteomyelitis ostectomy model was developed in which rats received a femoral bone defect with rigid plate-fixation. After fibrin-assisted transfer of Staphylococcus aureus (SA), effects of MSC implantation on osteomyelitis development were quantified over 3-4 weeks. All SA-infected animals developed an acute local osteomyelitis with significantly increased blood neutrophil count, abscess formation and bone destruction. MSC-treatment of infected defects aggravated osteomyelitis according to a significantly elevated osteomyelitis score and enhanced distal bone loss with spongy alteration of cortical bone architecture. Increased attraction of macrophages, osteoclasts and regulation of pro- and anti-inflammatory mediators were potential MSC actions. Overall trophic actions of MSCs implanted into non-sterile bone defects may enhance an infection and/or exacerbate osteomyelitis. Studies on antibiotic carrier augmentation or antibiotic treatment are warranted to decide whether MSC implantation is a safe and promising therapy for orthopedic implant-stabilized bone defects at high risk for development of infection.